Sociodrama-Based Play and Social-Emotional Development in Early Childhood: A Quasi-Experimental Study - Jhoni Warmansyah; Amina Ulya; Nur Rahma Hannia; Azizah Zain; Winda Trimelia Utami (Yayasan Keluarga Guru Mandiri, 2026)
Developing social-emotional competencies constitutes a core priority in early childhood education, as these competencies underpin children's capacity to manage their emotions, engage constructively with others, and build healthy interpersonal relationships. This study aims to examine the effect of positive emotional stimulation through sociodrama play on young children's social-emotional skills. Employing a quantitative framework, the research adopted a quasi-experimental pretest-posttest control-group design with participants aged 4-6 years, who were allocated equally to the experimental and control groups. Data collection relied on a structured observational instrument derived from the Social-Emotional Assessment/Evaluation Measure (SEAM), and data were analyzed using Analysis of Covariance (ANCOVA) in Jamovi to account for pre-existing group differences. Statistical outcomes revealed no significant difference between the two groups. Nonetheless, observational records indicated a discernible trend of growth across several social-emotional domains. While these developmental tendencies could not be confirmed statistically, the findings suggest that the observed gains were constrained by the conditions inherent to the study design. This investigation adds to the empirical literature on the capacity of structured sociodrama activities to nurture children's social-emotional growth.